Mobile-Nature of Science Model of Learning for Supporting Student Performance on General Chemistry Classroom - Khery, Yusran; Masjudin, Masjudin; Muzaki, Ahmad; Nufida, Baiq Asma; Lesnawati, Yesi; Rahayu, Sri; Setiawan, Nur Candra Eka (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Development of student understanding of nature of science, conceptual understanding, and scientific literacy on learning must be supported by proper learning process. An offline and online environment on mobile learning oriented with Nature of Science oriented learning can be considered to commit. Mobile-Nature of Science (Mobile-NOS) is suitable model of learning for this purpose. Evaluating the influence of Mobile-NOS model of learning application towards Students' understanding of nature of science, chemistry concept understanding, and scientific literacy on general chemistry learning are focus of this study. This study was carried out by posttest only control group design, in form of quasi experimental. There are 44 sample determined by saturated sampling technique of general chemistry students as population. Sample divided into two group equally, the experimental and control group. Data were collected by understanding nature of science questionnaire, scientific literacy test, and chemistry conceptual understanding test. Data was analyzed by independence sample t test. The result of the study showed that the application mobile-NOS model of learning make students better on understanding of nature of science, conceptual understanding, and scientific literacy